Myeloid/Lymphoid Neoplasm With FGFR1 Rearrangement Accompanying RUNX1 and NOTCH1 Gene Mutations - Wang, Xiaoxue; Huang, Xinyue; Pang, Hui; Xiao, Sheng; Gu, Hongcang; Zhang, Heyang; Wang, Baixun; Zhang, Lijun; Yan, Xiaojing (Frontiers in Oncology, 2019)
Background: Myeloid/Lymphoid Neoplasm with FGFR1 Rearrangement is a rare kind of hematological malignant disease. Case Presentation: A 37-year-old male patient experienced three distinct disease stages from myeloproliferative neoplasm (MPN), T-cell lymphoblastic lymphoma (T-LBL) to a much more complexed phage of a mixed phenotype acute leukemia (MPAL). Both genetic and genomic alternations were detected including chromosomal abnormality and genic mutations. Result: Karyotyping and fluorescence in situ hybridization (FISH) analysis of either bone marrow or lymph node sample confirmed the presence of the FGFR1 rearrangement. Amplifications of RUNX1, ERG and U2AF1 genes were identified by next generation sequencing. Furthermore, a frame-shift variant of F330fs*>149 in the RUNX1 gene and a missense mutation of R2263Q in NOTCH1 were also detected. Conclusion: The FGFR1 rearrangement functions as a trigging oncogenic event. Then other genetic events such as RUNX1 and/or NOTCH1 alternations further lead to progression of disease with trilineage blasts assignment.